Emotion
XI, 263 p.
Keywords: This unique collection provides a psychosocial approach to emotion, exploring the emotional undercurrents of everyday phenomena as diverse as war reporting, advertising, education, criminality, public policy and motherhood, and including contributors from sociology, psychology, cultural and media studies, and psychoanalytical studies.